Hashtag justice: Digital activism and the justice interests of school-related sexual violence survivors through the # HijaAko movement - Devesa, Bea Patricia (Asian journal of women's studies, 2025)
Digital activism has reshaped grassroots organizing, particularly in addressing sexual violence and institutional injustices experienced in educational institutions. This study examines the #HijaAko (roughly translated as “I am a young woman”) movement, a digital victims’ rights initiative in the Philippines, through the lenses of networked feminism. Central to this analysis is the concept of justice interests, which explores how victim-survivors conceptualize and pursue justice outside formal institutional mechanisms in educational institutions. Using interpretative phenomenological analysis (IPA) and qualitative participant narratives, this research investigates motivations, engagement dynamics, and the articulation of justice interests through digital activism. Findings indicate that student victim-survivors engaged in #HijaAko in response to failures of quasi-judicial mechanisms in addressing their justice claims. Digital activism provided validation, recognition, alternative pathways to accountability, and functioned as an affective counter-public where anonymity, affective testimony, and solidarity enable participants to reclaim epistemic authority and advance survivor-centered justice. Justice, as constituted within this space, emerges not as a linear process but as an iterative cycle of disclosure, solidarity, and agenda-setting. The paper expands scholarship on networked feminism and offers a re-evaluation of institutional responses to school-based sexual violence. KCI Citation Count: 0